The use of the PD-1/PD-L1 pathway as an immunotherapy in oncological diseases, autoimmune diseases and infectious diseases - Madras, Dominika Katarzyna; Rocka, Agata Agnieszka; Szumna, Klaudia Daria; Jasielski, Patryk Piotr; Piędel, Faustyna (Journal of Education, Health and Sport, 2020)
Introduction: PD-1 is programmed death receptor 1 belonging to the CD28 family of receptors. Immune cells have this receptor on their surface. PD-L1 allows cancer cells to avoid the host’s response. Connection to the PD-1 receptor leads to the death of the immune cell. Objective: The use of PD-1 receptors in the treatment of oncological, autoimmune and infectious diseases. Abbreviated description of the state of knowledge: The development and progression of immunotherapy in recent years has resulted in the approval of five immunotherapy pathways targeting PD-1 (pembrolizumab and durvalumab) or PD-L1 (atezolizumab, nivolumab and avelumab) in patients with progression during or after cisplatin based chemotherapy. The latest updates show that in some types of cancer, positive PD-L1 expression has an effect on treatment effect and qualification. These therapies are used, among others in melanoma, lymphomas, kidney cancer or breast cancer. PD-1 is also used to treat autoimmune and infectious diseases. Conclusions: Understanding the mechanism of the PD-1/PD-L1 pathway allows to design targeted therapy for individuals. It has been already used in NSCLC treatment program, whether bladder cancer or melanoma. Immunotherapy increases the survival time of patients with advanced stages of cancer. The therapies targeting the PD-1/PD-L1 pathway in autoimmune and infectious diseases are in clinical trials.